Appraisal of clinical practice guidelines on the management of obstetric perineal lacerations and care using the AGREE II instrument. (April 2020) - Nygaard, Christiana C.; Tsiapakidou, Sofia; Pape, Janna; Falconi, Gabriele; Betschart, Cornelia; Pergialiotis, Vasilios; Doumouchtsis, Stergios K.; ,; ,; ,
Abstract: Pelvic floor trauma during childbirth is highly prevalent and is associated with long term risks of incontinence and pelvic organ prolapse. Societies and organizations have published clinical guidelines in order to standardise and improve the management of perineal care. The aim of this study was to systematically evaluate the quality of clinical guidelines on obstetric perineal trauma and care using the AGREE II instrument. We searched Medline, PubMed, Web of Science and ScienceDirect databases from inception until the 15th of December 2018 using the terms "guideline" OR "guidelines", OR "guidance", OR "recommendation" AND "obstetric anal sphincter injury", OR "perineal laceration" OR "perineal tear" OR "perineal trauma" OR "vaginal tear". Twelve guidelines were included, in English and Spanish.The assessment of the guidelines was performed using AGREE II by 5 appraisers.Ten guidelines scored more than 50 %, and 3 of them scored higher than 70 %. Two guidelines scored <50 % and were considered as low quality. Level of evidence and grade of recommendations were used by 7 guidelines of the 12 guidelines. Although some guidelines received high scores, there is space for improvement of the standards of guidelines.